Pedagogical necessity of developing hygienic culture in preparing students for family life (Eurasian Journal of Learning and Academic Teaching, 2022)
The article talks about the pedagogical need to develop a hygienic culture in preparing students for family life. The main goal of the article is to achieve the development of young men and girls in family life and the provision of a healthy lifestyle